A Reflection on The Drowned and Oppressed Inheritance with an Approach to Imami Jurisprudence and the Laws of Iran, Egypt and Iraq. - abdoljabar zargoosh nasab; Masomah Hoseinzadah (مطالعات تطبیقی حقوق کشورهای اسلامی)
This research has investigated the inheritance of the dead in an accident and the unknown date of death of each of them in terms of Imami jurisprudence and the legal system of Iran, Egypt and Iraq. The condition of inheritance is the life of the heir, even a moment after the death of the heir, and the rest of the cases, that is, when several people have died at the same time, there will be no inheritance among them. Contrary to the above principle, is the life of the heir, it is after the death of the heir. According to this ruling, persons who have died due to drowning, and the date or precedence of which is not known, are inherited. Considering the importance of the circle of heirs and considering the public rights of the people, the present study has been written by referring to jurisprudential texts and collecting the opinions of Imami jurists, general jurists and jurists with a descriptive-analytical approach and explaining comprehensiveness or lack thereof. The above sentence has been extended to similar cases.